(untitled) (Journal of Economic Research & Business Administration, 2015)
The current research paper represents the work on building economic models for an open economy based on econometric functions which are used to characterize the state of national economy. The models are built based on statistical data of Republic of Kazakhstan covering the period from 2008 to 2011. As a result of this research paper the equilibrium values of key macroeconomic indicators have been obtained for the given external unregulated economic indicators and regulated economic instruments.